2018
DOI: 10.1002/2017jd027539
|View full text |Cite
|
Sign up to set email alerts
|

A 400‐Year Ice Core Melt Layer Record of Summertime Warming in the Alaska Range

Abstract: Warming in high‐elevation regions has societally important impacts on glacier mass balance, water resources, and sensitive alpine ecosystems, yet very few high‐elevation temperature records exist from the middle or high latitudes. While a variety of paleoproxy records provide critical temperature records from low elevations over recent centuries, melt layers preserved in alpine glaciers present an opportunity to develop calibrated, annually resolved temperature records from high elevations. Here we present a 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 108 publications
(219 reference statements)
3
27
0
Order By: Relevance
“…Using air temperature reanalysis and satellite infrared data, Williamson et al (2018) showed that in the St. Elias Mountains of southwest Yukon (608-628N, 1378-1428W), springtime (May) surface temperatures rose at rates from 0.148C a 21 at 1000 m to 0.198C a 21 at 5000 m during the years 2000-14. Farther west, analysis of melt layers (a proxy for summer warmth) in ice cores from Mount Hunter, Alaska (638N, 1518W), revealed an average warming trend at 3900 m of 0.02288 6 0.00448C a 21 between 1950 and 2011 (Winski et al 2018). Comparison to air temperature data from 15 lowelevation stations in Alaska and the Yukon suggests that summertime EDW is occurring on Mount Hunter.…”
Section: )mentioning
confidence: 99%
“…Using air temperature reanalysis and satellite infrared data, Williamson et al (2018) showed that in the St. Elias Mountains of southwest Yukon (608-628N, 1378-1428W), springtime (May) surface temperatures rose at rates from 0.148C a 21 at 1000 m to 0.198C a 21 at 5000 m during the years 2000-14. Farther west, analysis of melt layers (a proxy for summer warmth) in ice cores from Mount Hunter, Alaska (638N, 1518W), revealed an average warming trend at 3900 m of 0.02288 6 0.00448C a 21 between 1950 and 2011 (Winski et al 2018). Comparison to air temperature data from 15 lowelevation stations in Alaska and the Yukon suggests that summertime EDW is occurring on Mount Hunter.…”
Section: )mentioning
confidence: 99%
“…If diffusion lengths are sufficiently low relative to the annual layer thickness such that the annual cycle is preserved to the depth where vapor diffusion ceases to take place (e.g. at high accumulation locations in Alaska; see Winski et al, 2018), the annual cycle could be measureable for much greater timescales because solid diffusion is about four orders of magnitude slower than vapor diffusion (Johnsen et al, 2000). At this point, the limit likely becomes measurement resolution, or other physical factors, rather than diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…In more recent times, sporadic meteorological measurements on or near Denali have been carried out in the context of glaciological studies at lower elevations, for example, on the Kahiltna Glacier (Young et al 2018), or for brief periods of time during scientific expeditions, for example, on the summit plateau of Mount Hunter during the drilling of glacial ice cores (Winski et al 2018;Osterberg et al 2017;Saylor et al 2014). Winski et al (2018) use temperature data collected in 2013 and 2015 on Mount Hunter to determine the distribution of summer temperatures at the drill site, which informs the analysis of melt layers in the ice core and the development of a long-term temperature record, providing valuable insights into Holocene climate in the Denali region and beyond. The ice core analysis suggests a summertime warming rate of 1.928 6 0.318C in the last century, which exceeds typical warming rates at lowerelevation sites of similar latitude and is in the same range as a temperature increase of 0.028C yr 21 found by Hartl et al (2020a) from NCEP-NCAR reanalysis data (Kalnay et al 1996).…”
Section: B Aws Location and Previous Meteorological Measurements On mentioning
confidence: 99%
“…Existing data are all the more valuable and serve to improve understanding of important atmospheric and climatic processes (e.g., Marty and Meister 2012;Ohmura 2012;Rangwala and Miller 2012), as well as ground-atmosphere interactions, for example, in the context of local catchments, regional hydrology, and the high-mountain cryosphere (e.g., Immerzeel et al 2014;Shea et al 2015;Immerzeel et al 2020;Litt et al 2019). Data records from high-elevation mountain AWS have proven essential for delineating drivers of local glaciological processes (Salerno et al 2015) and are important for the calibration of proxy data such as ice cores from mountain glaciers to atmospheric variability (Hardy et al 1998;Osterberg et al 2017;Winski et al 2018;Bohleber 2019). Under ongoing climate change, mountain environments are changing rapidly, with potentially dramatic consequences for local populations affected by related natural hazards or downstream communities reliant on mountain-fed river systems (Hock et al 2019;Immerzeel et al 2020).…”
Section: Introductionmentioning
confidence: 99%